Genetic and morphological analyses of Ngongok fish (Hampala macrolepidota) from Ngebel Lake, Ponorogo District, Indonesia - ELOK AMALIA; AKHSAN FIKRILLAH PARICAHYA; MUHAMMAD DAILAMI; ABDUL RAHEM FAQIH; WAHYU ENDRA KUSUMA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Amalia E, Paricahya AF, Dailami M, Faqih AR, Kusuma WE. 2026. Genetic and morphological analyses of Ngongok fish (Hampala macrolepidota) from Ngebel Lake, Ponorogo District, Indonesia. Biodiversitas 27 (4): d270410. https://doi.org/10.13057/biodiv/d270410. Hampala macrolepidota is a freshwater fish widely distributed in Southeast Asia and plays an important ecological and economic role. However, increasing anthropogenic pressures raise concerns about population structure and genetic integrity. This study aimed to confirm species identity and assess genetic diversity and population differentiation using an integrated morphological and molecular approach. Specimens were collected from Ngebel Lake (Ponorogo, East Java) and compared with populations from East Java, South Sumatra, and Thailand. The morphological identification and inventory profile of H. macrolepidota, combined with genetic studies based on Cytochrome b (Cytb) of mitochondrial DNA (mtDNA) at the population level in Ngebel Lake, have not been explored before. Ngongok fish in Ngebel Lake has been confirmed as H. macrolepidota based on morphological and genetic studies. H. macrolepidota sequences from Ngebel Lake represent the Insular Asia region separated from the Mainland Asia region population based on haplotype network, phylogenetics, and genetic p-distance measurements. The H. macrolepidota population in Ngebel Lake has historically experienced rapid growth, as indicated by high genetic diversity (hd = 1.0000, π = 0.0086) and a favorable demographic history (D = 0.6479, Fs = -0.4208). The genetic closeness of H. macrolepidota and Cyprinus carpio presents potential for hybridization in the future. Despite morphological similarity across regions, genetic divergence highlights the importance of molecular data in resolving population-level differences. These findings suggest that H. macrolepidota populations are shaped by geographic and biogeographic barriers, with potential implications for conservation and management. The observed genetic patterns also suggest a potential hybridization risk under increasing environmental pressure, although further investigation using nuclear markers is required.